The Effectiveness of Behavioral Counseling Services Using Self-Management Techniques in Reducing Online Gaming Addiction Behaviors in Adolescents - Azmatun Sholikha; Nadia Ayu Widiasari; Rajip Albar Maulana; Naeila Rifatil Muna; Hamasah Al Maqdis Mabruri (Al-Musyrif)
Adolescence is a phase of transition from childhood to adulthood. At this time, changes usually occur in the form of body, cognitive, and psychology. Today’s teenagers are the generation that understands technology the most because they are raised with technology that is very easily accessible. This can have a bad impact if not addressed properly and correctly. One example is addiction to playing Online Games. Excessive playing of Online Games can cause problems such as loss of ability in time management, withdrawing from social activities, loss of academic value and other important life roles. To deal with the problem of Online Game addiction in adolescents, a counseling program needs to be provided. Counseling services provided can be carried out with a Behavioral Counseling approach. This study aims to identify how behavioral counseling services with a self-management approach can be effective in reducing Online Game addiction in adolescents. With a literature review approach using documentation and content analysis techniques, this study found that Self-management Techniques, both intervened through individual and group counseling, have proven to be effective in reducing Online Game addiction behavior in adolescents from various levels of education (junior and senior high school).